Wound Healing potential of Grandiflorenic Acid Isolated from Wedelia trilobata Linn. - Kavachale, Aayushi; Shrivastava, Taru; Balekar, Neelam (Journal of Drug Delivery and Therapeutics, 2017)
The ethyl acetate fraction from ethanolic extract of W. trilobata leaves displayed antibacterial and fibroblast stimulatory activities thereby suggesting potential wound healing properties. Ethyl acetate fraction was further subjected to bioassay guided fractionation, which afforded isolation of grandiflorenic acid (GA). GA exhibited potential in vitro wound healing activity due to fibroblast stimulation and inhibiting inflammatory phase of wound healing, evident by reduced levels of inflammatory cytokines from macrophage RAW 264.7 cells. The aim of the present study was to evaluate wound healing activity of GA formulated in ointment base (0.5% and 1.0% w/w) using excision, incision and dead space wound models in experimental rats. Treatment of wound with isolated grandiflorenic acid 1.0% w/w topically exhibited significant (p<0.01) wound healing activity in all three models as compared to control groups. High rate of wound contraction, decrease in period of epithelialisation, high tensile strength, increase in dry granulation tissue weight.